From employability skills to workplace performance: The mediating role of career adaptability in employer evaluations of student trainees - Rodelas, Allan Nicko (Journal of Interdisciplinary Studies in Education, 2026)
This study examined the relationship between college students’ perceived employability skills and their employability and competencies as evaluated by their on-the-job training (OJT) hosts, with career adaptability behavior as a mediator. Using data from 317 students and structural equation modeling (SEM), the results showed that students generally demonstrated moderate to high levels of employability skills, career adaptability, and employability. Use of technology showed no significant relationship with employability, whereas multitasking influenced employability indirectly through career adaptability. Oral communication and disciplinary expertise were fully mediated by career adaptability, whereas ethics and responsibility and interpersonal skills were partially mediated. The findings highlight the crucial role of career adaptability in translating employability skills into positive employer evaluations.